Dose-dense weekly chemotherapy in advanced ovarian cancer: An updated meta-analysis of randomized controlled trials. (May 2018) - Marchetti, C.; De Felice, F.; Di Pinto, A.; D'Oria, O.; Aleksa, N.; Musella, A.; Palaia, I.; Muzii, L.; Tombolini, V.; Benedetti Panici, P.
Highlights: Adjuvant 3-weekly carboplatin and paclitaxel is the first-line therapy in advanced ovarian cancer (OC). The role of dose-dense chemotherapy as alternative regimen needs to be confirmed. This updated meta-analysis compares dose-dense chemotherapy versus standard treatment. This meta-analysis suggests that 3-weekly carboplatin and paclitaxel should remain the standard. Abstract: Objective: The use of dose-dense weekly chemotherapy in the management of advanced ovarian cancer (OC) remains controversial. The aim of this meta-analysis was to evaluate the efficacy of dose-dense regimen to improve clinical outcomes in OC patients with the inclusion of new trials. Methods: For this updated meta-analysis, PubMed Medline and Scopus databases and meeting proceedings were searched for eligible studies with the limitation of randomized controlled trials, comparing dose-dense chemotherapy versus standard treatment. Trials were grouped in two types of dose-dense chemotherapy: weekly dose-dense (both paclitaxel and carboplatin weekly administration) and semi-weekly dose-dense (weekly paclitaxel and three weekly carboplatin administration). Data were extracted independently and were analyzed using RevMan statistical software version 5.3 (http://www.cochrane.org ). Primary end-point was progression-free survival (PFS). Results: Four randomized controlled trials comprising 3698 patients were identified as eligible. Dose-dense chemotherapy had not a significant benefit on PFS (HR 0.92, 95% CI 0.81–1.04, p = 0.20). When the analysis was restricted to both weekly and semi-weekly dose-dense data, a no significant interaction between dose-dense and standard regimen was confirmed (HR 1.01, 95% CI 0.93–1.10 and HR 0.82, 95% CI 0.63–1.08, respectively). Conclusions: In the absence of PFS superiority of dose-dense schedule, three weekly schedule should remain the standard of care for advanced OC.